Thyroid nodule with cytological outcome of indeterminate lesion with low risk of malignancy found to be parathyroid adenoma. A case report and minireview of literature - Meomartino, Letizia; Rossi, Mattia; Selvatico, Gloria; Rossetto Giaccherino, Ruth; Pagano, Loredana (Frontiers in Endocrinology, 2025)
Primary hyperparathyroidism (PHPT) is the third most common endocrine disorder, typically caused by a single parathyroid adenoma. The diagnosis of PHPT is biochemical, and the localization of abnormal parathyroid glands is usually achieved through a combination of ultrasound and technetium-99m sestamibi (99mTc-MIBI) scans. In some cases, newer imaging modalities, such as positron emission tomography-computed tomography (PET-CT) with 18F-fluorocholine or 11C-methionine, are used as second-line methods. Consequently, parathyroid tissue (PTT) is not typically sampled by fine needle aspiration biopsy (FNAb). However, with an incidence ranging from 9% to 22%, the affected parathyroid gland may present in an ectopic location, with the thyroid gland being a possible site. In intra-thyroidal parathyroid adenomas (IPAs), the differential diagnosis with thyroid nodules can be challenging due to similar ultrasound features and the potential uptake of 99mTc-MIBI by some thyroid nodules. As a result, such lesions may sometimes undergo unintentional cytological examination, leading to the risk of misinterpretation as cytologically indeterminate thyroid lesions. This can result in both misdiagnosis and inappropriate surgical approach. For this reason, a routine evaluation of calcium-phosphorus metabolism could prove beneficial as part of the diagnostic workup for cytologically indeterminate thyroid nodules, especially when surgery is planned. To support this diagnostic approach, we present a mini-review of the literature on this topic, along with a case report of an IPA misinterpreted as an indeterminate thyroid lesion (TIR3A, according to the Italian Society for Anatomic Pathology and Cytology–Italian Thyroid Association 2014 classification system), diagnosed following the preoperative incidental detection of hypercalcemic PHPT.